Aprendizaje basado en problemas vs clase conferencia en el rendimiento del curso de estadística aplicada: estudiantes de la facultad de ciencias económicas, contables y administrativas en la Universidad Nacional de Cajamarca - 2015 - Cárdenas Rodríguez, Karina Jacqueline (2016)
ABSTRACT This research, of applied nature, aimed to determine the effect of teaching methods: Problem-Based Learning vs. Class Conference, on the performance of students of the subjects Applied Statistics in the Faculty of Economics, Accounting and Management of the National University of Cajamarca in 2015; for the which he worked with a random sample of students from the Schools Academic Professionals in Economics, Accounting and Administration, considered as blocks and randomly selecting within each school the students to receive the contents of the second unit of the subject with the Problem Based Learning methods and Class Conference, taking note of the first unit as a co-variate, being the response variable note end of the subject, so the co-variance model was used in a design block completely random. A highly significant difference was found in the two methods, being the best Problem Based Learning, they also found a highly significant difference in the final grade for the course Statistics Applied student, after removing the effect of the initial note subject, which also turned out to be highly significant in the final grade, the I justify the use of the indicated model.